Observations on age at marriage in Dublin, related to social status and social mobility - Hutchins, B (Economic & Social Studies, 1971)
The years since the Second World War have been characterised by a general decline in mean age at marriage in the Western world: people are marrying at earlier ages than was usual in the immediate past. Ireland has proved no exception, for although this country has been (and indeed remains) outstanding in the European context for its high mean age at marriage, available statistics show that Ireland is following the general fashion for younger marriages. A comparison with the relevant figures for Denmark and the Netherlands (selected for comparison because of a certain similarity to Ireland in population size and economic character) shows a decrease, during the years 1959-1967, of roughly two years in mean age at marriage in all three countries.
Keywords: Marriage age